The Baligraphy on Wood Craft: - - I Kadek Gita Rismawan; I Nyoman Sila; I Gusti Made Budiarta (Universitas Pendidikan Ganesha, 2026)
Baligraphy is known as the art of beautiful writing combined with Balinese script with the presence of a form that is its characteristic. The beginning of the emergence of this writing art when the concern of an expert in ancient Javanese literature at UNUD regarding the loss of Balinese language education in the educational realm. Baligraphy is the art of beautiful writing that combines Balinese script, literature, visual arts, and jnana. In the creation of Baligraphy writing art as a source of ideas or inspiration as well as the revitalization of Baligraphy in wood craft art with carving techniques. This study has the aim to describe 1) the concept of creating Baligraphy in wood craft, 2) the process of creating Baligraphy in wood craft from the perspective of materials, and preparation of tools, 3) the results and meaning of Baligraphy visualization that harmonizes four elements: script, literature, visual arts and jnana. The method used is Practice Based Research (PBR) with a qualitative descriptive method. This study uses several data collection techniques namely observation, literature study, interviews, documentation and library research. The results of the study obtained data on the concept of creating works through the form of imagery play in words, visuals, sounds, stories or events, informant research and literature studies. The process of creating wood craft works from the stage of determining ideas, making sketches, transferring sketches, carving/engraving, coloring and coating the work. The results and meaning of Baligraphy visualization in the creation of Baligraphy works in Wood Craft, consisting of Bhur (physical realm), Bhuvah (mental realm), Svah (soul realm) which have their own meaning in each work.